The determination of the carriers recombination parameters based on the HOT HgCdTe current-voltage characteristics - Manyk, Tetiana; Rutkowski, Jarosław; Madejczyk, Paweł; Gawron, Waldemar; Martyniuk, Piotr (Opto-Electronics Review, 2022)
A theoretical analysis of the mid-wavelength infrared range detectors based on the HgCdTe materials for high operating temperatures is presented. Numerical calculations were compared with the experimental data for HgCdTe heterostructures grown by the MOCVD on the GaAs substrates. Theoretical modelling was performed by the commercial platform SimuAPSYS (Crosslight). SimuAPSYS fully supports numerical simulations and helps understand the mechanisms occurring in the detector structures. Theoretical estimates were compared with the dark current density experimental data at the selected characteristic temperatures: 230 K and 300 K. The proper agreement between theoretical and experimental data was reached by changing Auger-1 and Auger-7 recombination rates and Shockley-Read-Hall carrier lifetime. The level of the match was confirmed by a theoretical evaluation of the current responsivity and zero-bias dynamic resistance area product (R0A) of the tested detectors.